A Rare Case of Ectopic Ureter Presenting as Scrotal Abscess - Dhangar, Dr. Sanjay P. (SP'z Series New Insights on Urology and Urological Research Part I, 2022)
Single system ureteral ectopia is rare. It is more commonly found in males. It is defined as any ureter, single or duplex, that does not enter the trigonal area of the bladder. In females the ectopic ureter may enter anywhere from the bladder neck to the perineum and into the vagina, uterus, and even rectum. In males the ectopic ureter always enters the urogenital system above the external sphincter or pelvic floor and usually into the wolffian structures including vas deferens, seminal vesicles, or ejaculatory duct. The presentation is variable. Males do not present with incontinence but with infection and pain of the affected organs e.g. testicles and epididymis and females usually present with incontinence of urine. We here present a rare case of ectopic ureter that presented to us as scrotal abscess. Keywords: Ectopic ureter; Ureteric reimplantation; Scrotal abscess; Ureter opening into prostatic urethra.